2017
DOI: 10.1002/eat.22796
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and correlates of exercise among adolescents with anorexia nervosa and bulimia nervosa

Abstract: Objective To characterize exercise behaviors among adolescents with anorexia nervosa (AN), atypical AN, or bulimia nervosa (BN), and determine associations between exercise and medical risk. Study design Cross-sectional electronic medical records of all patients evaluated by the Eating Disorder Program at Stanford between January 1997 and February 2011 were retrospectively reviewed. Results 1,083 subjects (961 females, 122 males; mean age 15.6) met eligibility criteria. Most patients (89.7%) reported exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 56 publications
0
20
1
2
Order By: Relevance
“…A recent study among university students from the United Arab Emirates (UAE) also found that a higher proportion of females were dissatisfied with their body size, whereby females desired to lose weight and preferred diet to exercise, and males desired to gain weight and preferred exercise to diet [38]. Future DE assessment may need to consider examining compulsive exercise [39] and androgenic anabolic steroid use [40], which may be more prevalent among male young adults. In the present study, higher body size dissatisfaction and poorer body appreciation contributed significantly to DE in female students, but not in male students.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study among university students from the United Arab Emirates (UAE) also found that a higher proportion of females were dissatisfied with their body size, whereby females desired to lose weight and preferred diet to exercise, and males desired to gain weight and preferred exercise to diet [38]. Future DE assessment may need to consider examining compulsive exercise [39] and androgenic anabolic steroid use [40], which may be more prevalent among male young adults. In the present study, higher body size dissatisfaction and poorer body appreciation contributed significantly to DE in female students, but not in male students.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 Questions related to vomiting, fasting or skipping meals, diuretics, and laxative use that served as a proxy for unhealthy weight control behaviors represent thinness-oriented goals, which may be more relevant to females. Future research could examine sex differences [42][43][44] in compulsive exercise 45 or androgenic anabolic steroid use, 46 which may be more prevalent among young adult men than women considered overweight or obese.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, weight‐related sports, or sports in which it is important to stay a certain weight, such as wrestling, rowing, or gymnastics, have been shown to be associated with greater odds of AAS use (Vertalino, Eisenberg, Story, & Neumark‐Sztainer, ). Sports team participation and greater frequency of exercise has been shown to be associated with greater medical instability (as measured by bradycardia) among adolescents with anorexia nervosa or bulimia nervosa (Nagata et al, ).…”
Section: Discussionmentioning
confidence: 99%